Tinjauan Yuridis Atas Implementasi Registrasi PSAT-PDUK Sebagai Instrumen Hukum Dalam Menjamin Keamanan Pangan Di Indonesia - Divanda Permata Wijayatama; Sapto Hermawan; Asianto Nugroho (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
Food safety is a crucial aspect of consumer protection and national food security. Registration of Fresh Food from Plants of Domestic Production of Small Businesses (PSAT-PDUK Registration) is regulated as a form of legal instrument to ensure that fresh food in circulation meets quality and safety standards. This article aims to analyze the regulation of PSAT-PDUK registration in Indonesia from a legal perspective and review the effectiveness of its implementation. The method used is normative juridical with the approach of legislation and legal theory of consumer protection. The results of the study show that despite being regulated in the Food Law, Government Regulation No. 86/2019, Government Regulation No. 5-2021, MOA No. 53/2018, and other technical implementing regulations, the implementation of PSAT-PDUK registration still faces a number of obstacles such as low literacy of small business actors, limited supervision, and not optimal synergy between supervisory institutions. Therefore, it is necessary to strengthen the role of the Food Safety Competent Authority (OKKP) and harmonize regulations in order to increase the effectiveness of the implementation of PSAT-PDUK Registration as a legal instrument of the government in guaranteeing and monitoring food safety of Fresh Food of Plant Origin in public circulation.